Evolution of the Palms (Terric Haplosaprist) soil in Iowa, 1969 to 2001 - Larabee, Beth Elaine (Iowa State University Digital Repository, 2005)
Throughout the 20th century, soil surveys have shown Histosols to be extensive across the Des Moines Lobe, which is a Late Wisconsinan glacial surface that covers more than 50,000 km2 of Iowa and Minnesota. Current anecdotal evidence suggests many Histosols underwent considerable degradation throughout the late 20th century due to human induced lowered water tables and erosion. The objective of the project was to document whether the Palms soils (loamy mixed euic mesic Terric Haplosaprist) have in fact changed over the last 30 years. The Palms series was selected for the study because it is the most common Histosol on the Des Moines Lobe (DML) in Iowa. Field methods consisted of two components. The first was sampling and describing three deep soil cores within a 50 cm radius from of each of 15 national Cooperative Soil Survey (NCSS) typical pedon locations in Iowa. The earliest NCSS pedon was described in 1969 while the most recent one was described in 1999. The second was evaluating the spatial distribution of histic morphology of the Haplosaprist map units. This study has a 31-year timeline for comparison. Key results are all pedons lost histic material with eight sites remaining Histosols and five sites having just histic epipedons. One site now has a mineral epipedon. The mean reduction of histic material thickness was 38.8 cm, and bulk density of histic materials averaged 0.5 Mg*m−3. In conclusion, the Palms series has been dramatically degraded over the past 30 years. Extending these results it appears likely that over the next 30 years no Histosols will remain in cropped areas of the DML, or possibly the whole of Iowa.